The discovery of 64 luminous infrared galaxies in the LAMOST Complete Spectroscopic Survey of Pointing Area at the Southern Galactic Cap. (August 2015) - Lam, Man I; Wu, Hong; Yang, Ming; Zhu, Yi-Nan; Shi, Jian-Rong; Zhang, Hao-Tong; Luo, A-Li; Shen, Shi-Yin; Zhang, Yong; Hou, Yong-Hui; Li, Guang-Wei; Zhao, Yong-Heng
Abstract We report the discovery of 64 luminous infrared galaxies, based on new observations of 20 square degrees from the LAMOST Complete Spectroscopic Survey of Pointing Area at the Southern Galactic Cap and the WISE 22 μm catalog from the AllWISE Data Release. Half of them are classified as late-type spirals and the others are classified as peculiar/compact galaxies. The peculiar/compact galaxies tend to exhibit higher luminosities and lower stellar masses. We also separate AGNs from HII galaxies in a simple way by examining LAMOST spectra. Those cases show that host AGNs are easily distinguished from others in the mid-infrared color-color diagrams.